DAMPAK PENGATURAN BARIS TANAM JAGUNG ( Zea mays L.) DAN POPULASI KACANG HIJAU (Phaseolus radiatus L.) DALAM TUMPANGSARI TERHADAP PERTUMBUHAN DAN HASIL KACANG HIJAU, JAGUNG - - Sucipto (Universitas Trunojoyo Madura, 2009)
Many factors that must be consideredIn the intercropping system, especially competition between the mixed crop, both for growth and the development of plants. Various forms of interaction between plants in the agricultural environment has often been interpreted as a competition. Competition occurs in a population when there is competition, which affects the growth factors such as sunlight, water, nutrients, CO2 and other gases. Research goals to determine response of green beans and the impact of the treatment populations of green beans and corn planting rows. This reseach use factorial design arranged in randomized block design with three replications, factor I is a population of green beans, with 4 levels, namely: A1: Population sprawl (35cm x 30cm); A2: Population's (30cm x 25cm); A3 : Population enough (25cm x 20cm) and A4: Population solid (20cm x 15cm). Factor II, namely corn rows with two levels, namely: B1: Single line and B2: the double line .. The observed parameters include non destructive observations of plant height, number of leaves and stem diameter; Observation of destructive plant dry weight, seed dry weight, number of seeds, planting and number of pods. The results of treatment research affect the population of green bean green bean plants on plant height, stem diameter, number of leaves, plant dry weight, seed dry weight, number of seeds, and the number of pods. While the influence of maize plants at the stem diameter, number of seeds and seed dry weight. For planting rows of corn plants affect plant green beans on the plant height, stem diameter, number of leaves, dry weight, seed dry weight and number of seeds, and the corn plants affect the stem diameter, number of seeds, and seed dry weight.